Reduced neutralizing antibody potency of COVID‐19 convalescent vaccinated plasma against SARS‐CoV‐2 Omicron variant. Issue 7 (16th May 2022) - Gallian, Pierre; Amroun, Abdennour; Laperche, Syria; Le Cam, Sophie; Brisbarre, Nadège; Malard, Lucile; Nurtop, Elif; Isnard, Christine; Richard, Pascale; Morel, Pascal; Tiberghien, Pierre; de Lamballerie, Xavier
Abstract: Background and Objective: The SARS‐CoV‐2 Omicron variant displays increased infectiveness as well as mutations resulting in reduced neutralizing activity of antibodies acquired after vaccination or infection involving earlier strains. To assess the ability of vaccinated COVID‐19 convalescent plasma (CCP‐V) collected before November 2021 to seroneutralize Omicron, we compared neutralizing antibody (nAb) titres of 63 samples against Omicron and earlier B.1 (D614G) strains. Methods and Findings: Relationship between anti‐Omicron titres and IgG anti‐S1 levels (binding arbitrary unit: BAU/ml) was studied. Although correlated, anti‐Omicron titres were significantly lower than anti‐B.1 titres (median = 80 [10–1280] vs. 1280 [160–10, 240], p  < 0.0001). Omicron nAb titres and IgG anti‐S1 levels were correlated (Spearman's rank correlation coefficient = 0.67). Anti‐S1 IgG threshold at 7000 BAU/ml may allow to discard CCP‐V without anti‐Omicron activity (nAb titre <40). Conversely, only those with highest titres (≥160) had systematically anti‐S1 IgG levels >7000 BAU/ml. Conclusion: A fraction of CCP‐V collected before November 2021 retains anti‐Omicron seroneutralizing activity that may be selected by quantitative anti‐IgG assays, but such assays do not easily allow the identification of 'high‐titre' CCP‐V. However, collecting plasma from vaccinated donors recently infected with Omicron may be the best option to provide optimal CCP‐V for immunocompromised patients infected with this variant.